2005
DOI: 10.1080/09581590500372121
|View full text |Cite
|
Sign up to set email alerts
|

An ecological model for understanding culture as a determinant of women's health

Abstract: In combination with gender and culture, the authors argue that the migratory experience must be considered as a determinant of the health of immigrant women in its own right. Gender and other symbolic institutions are seen as intertwined in an ecological model of health. Bronfenbrenner's (1986) systems theory and a combination of theories of social cognition, social exchange and symbolic interaction articulated by Howard and Hollander (1997) expand the ecological model. Cognitive schemas of gender and culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 58 publications
1
61
0
2
Order By: Relevance
“…While housing insecurity is often discussed in terms of economic instability, the woman's sense of security for herself and her children were explicitly considered in the definition for our study. The conceptual framework we used included an ecological model of gender, migration and health (Thurston & Vissandjée, 2005); gender has been ignored in many studies on migration (Tastsoglou, Ray, & Preston, 2005), but was made explicit in this framework. The interplay of systemic factors with individual factors was also made explicit.…”
Section: Conceptual Framework and Research Questionsmentioning
confidence: 99%
“…While housing insecurity is often discussed in terms of economic instability, the woman's sense of security for herself and her children were explicitly considered in the definition for our study. The conceptual framework we used included an ecological model of gender, migration and health (Thurston & Vissandjée, 2005); gender has been ignored in many studies on migration (Tastsoglou, Ray, & Preston, 2005), but was made explicit in this framework. The interplay of systemic factors with individual factors was also made explicit.…”
Section: Conceptual Framework and Research Questionsmentioning
confidence: 99%
“…This book also depicts the dilemmas of feminist action research in illustrating how social action and empowerment could be out of the control of the researcher despite her best intentions to generate social transformation. This book reinforces the urgency for nurses to examine issues of health inequities stemming from social injustice by using ecologic and social activist theoretical and methodological approaches to speak to power and fulfill nursing's social and ethical mission through engaged research as suggested by some nurse scholars (Falk-Rafael, 2005;Giddings, 2005;Thurston & Vissandjée, 2005 The Wounds of Exclusion Poverty, Women's Health, and Social Justice (Reid, 2004) may be overlooked by American nurses because its author is not a nurse and because it describes research conducted in Canada. Such an oversight would represent a significant loss for those nurse scholars concerned with the challenges of health promotion and socioeconomic disparities in health status.…”
mentioning
confidence: 74%
“…Furthermore, it facilitates reflection on the inextricable link between historical events and current inequities, something that is pertinent to the discussion of culture and health in the Amazon31. As a tool that recognizes the complex links between an individual and their environment and positions the individual at the centre of multi-level health determinants, it functions in complement to the ecological framework for health [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Through this lens, modern communicable epidemics such as HIV/AIDS and tuberculosis are positioned as inseparable from, and a result of, ‘violent’ socioeconomic structures [12,13]. More recently, Montesanti and Thurston overlaid the concept of structural violence onto an ecological framework for health [22] by mapping the role of symbolic, structural, and interpersonal violence on women’s lives [23]. Through this process, intersecting social determinants of health are linked both to structural violence and to individual health outcomes, including interpersonal violence (Figure 1) [23].…”
Section: Designmentioning
confidence: 99%